Locoregional Therapy Protocols With and Without Radioembolization for Hepatocellular Carcinoma as Bridge to Liver Transplantation. (May 2020) - Zori, Andreas G.; Ismael, Media N.; Limaye, Alpna R.; Firpi, Roberto; Morelli, Giuseppe; Soldevila-Pico, Consuelo; Suman, Amitabh; Vogel, Jeffrey D.; Lazarowicz, Michael; Geller, Brian S.; Toskich, Beau; Gonzalo, David H.; et al.
Abstract : Objective: The objective of this study was to compare posttransplant outcomes in patients undergoing bridging locoregional therapy (LRT) with Y-90 transarterial radioembolization (TARE) based protocol compared with transarterial chemoembolization based protocol for hepatocellular carcinoma (HCC) prior liver transplantation (LT). Materials and Methods: Patients listed for LT with HCC within the Milan criteria at our center who had bridging LRT were treated according to transarterial chemoembolization (TACE) based protocol from May 2012 to April 2014 and a TARE based protocol from October 2014 to December 2017. Early posttransplant survival and tumor recurrence were compared between the groups. Tumor response to LRT, microvascular invasion (mVI), and the rate of delisting was also evaluated. Results: One hundred three patients who were listed for LT with HCC within the Milan criteria received LRT. LT was performed in 65 patients, 28 treated with TARE protocol and 37 on TACE protocol. There were no statistical differences in baseline pretransplant characteristics and tumor recurrence. There was a trend toward improved 3-year survival in the TARE group (92.9% vs. 75.7%; P =0.052). The mVI was seen in 1/28 (3.6%) explants in the TARE group compared with 10/37 (27%) in the TACE group ( P =0.013). The TARE group also required fewer LRT treatments (1.46 vs. 2.43; P =0.001) despite no difference in time on the transplant list. Conclusions: Despite requiring fewer LRT treatments, there was significantly less mVI in the explants of patients treated with TARE protocol LRT as a bridge to LT as well as a trend toward improved 3-year survival. Therefore, TARE may be associated with improved tumor control and reduced post-LT recurrence.